A gap is filled: First structures of enantiopure iron(III) complexes with Schiff base ligands derived from ortho-vanillin and l-glutamine or l-glutamic acid. (1st April 2018) - Muche, Simon; Harms, Klaus; Burghaus, Olaf; Hołyńska, Małgorzata
Graphical abstract: Synthesis, characterization and crystal structures of an ligand derived from ortho -vanillin andl -glutamine as well as four novel high spin iron(III) complexes derived from ortho -vanillin andl -glutamine orl -glutamic acid. Crystal structures provided for three complexes. Abstract: A series of new Fe(III) complexes, [Fe(OVGln)2 ]Na (1 ), [Fe(OVGln)2 ]K (2 ), [Fe(OVGlu)2 ]Na (3 ) and [Fe(OVGlu)2 ]K (4 ), with Schiff base ligand derived from ortho -vanillin (OV) andl -glutamine (Gln) orl -glutamic acid (Glu), are presented. The complexes are extensively characterized with mass spectrometry, IR spectroscopy, X-ray powder diffraction, EPR and elemental analysis. Three complexes are additionally characterized with single crystal X-ray diffraction analysis. The mononuclear complexes are anionic with sodium or potassium as counterions. Depending on the nature of the amino acid within the ligands and the counterions, varying arrangements of the complex anions in the crystal structures can be observed. The synthesis procedure and full characterization data for one of the applied ligands in form of its disodium salt (OVGlnHNa2 ) are also provided.